Diversity and conservation status of small non-volant mammals of Loreto, Peru - Sánchez-Vendizú, Pamela (2021)
In this work, we conducted an exhaustive review of databases of scientific collections and specialized literature with the goal to update the list of the smaller non-volant mammals (<1000 g approx.) of the department of Loreto. Results show 536 localities where are including records of 75 species, grouped in four orders and six families, this represent to 13% and 28.6% of the mammal diversity of Peru and Loreto, respectively. In addition, five of the 83 endemic mammal species of Peru occur in Loreto: Akodon orophilus, Neusticomys peruviensis, Hadrosciurus "species 3", Marmosops (Marmosops) soinii and Monodelphis (Mygalodelphys) handleyi; the last three species are only recorded in this department. Likewise, 23 species are considered rare and 12 common. In addition, two are considered Vulnerable and three as Data Deficient by Peruvian legislation, and about 16 species have not been evaluated by the International Union for Conservation of Nature (IUCN). On the other hand, while the species diversity of small non-volant mammals is comparatively well represented in the different provinces of Loreto, Putumayo province is the least explored with only 10 species. In addition, five large areas of information gaps were found, distributed mainly in the border areas: 1) the entire province of Putumayo and northeast of Maynas, 2) south of the Amazon River in the province of Mariscal Ramón Castilla, 3) north of the province of Datem del Marañón, 4) southwest of Datem del Marañón and 5) south and west of the province of Ucayali, which explain why the diversity of this group is largely underestimated in this department.